Peripheral milling machines in wood industry / Muhammad Rizal B. Abdullah - B. Abdullah, Muhammad Rizal (2003)
The machined surface may be flat, angular, or curved. The surface may also be milled to any combination of shapes. The machine for holding the work piece, rotating the cutter, and feeding it is known as the milling machine. In peripheral (or slab) milling, the milled surface is generated by teeth located on the periphery of the cutter body. Milling cutters are available in many standard and special types, forms, diameters, and widths. The teeth maybe straight (parallel to the axis of rotation) or at a helix angle. CNC expert covers the key factors behind making controls and the entire milling process move faster. A high speed control will gives you the ability to finish one task faster and move along to the next sooner. In drilling and tapping, this can result in faster hole-to hole times, quicker spindle reversals for tapping, and substantial cycle-time reductions. Various milling machine components are being replaced rapidly with computer numerical control (CNC) machines. These machine tools are versatile and are capable of milling, drilling, boring and tapping with repetitive accuracy.